UberPop, UberBlack, and the regulation of digital platforms after the Asociación Profesional Elite Taxi judgment of the CJEU: judgment of the Court (Grand Chamber) 20 December 2017, Asociación Profesional Elite Taxi (C-434/15) - Philipp Hacker (aEuropean Review of Contract Law (ERCL), 2018)
The case concerning a smartphone transport application provided by Uber, decided by the Grand Chamber of the CJEU on 20 December 2017, has the potential to reshape the regulation of contracting in the digital economy. More precisely, it specifies the rules applicable to online platforms serving as intermediaries between parties demanding and offering services. The criteria the CJEU uses to reach its conclusion are likely to have repercussions far beyond the area of transportation applications. This Case Note starts by presenting the facts of the case and the legal background of those EU law provisions potentially governing digital intermediaries. It then explores the criteria the Court uses to distinguish Uber from simple intermediation services, followed by a discussion and critique of these criteria. In the last two sections, it maps out the implications of the judgment for the platform economy, and suggests that a decisive impetus of the judgment should be a thorough review of regulations governing the provision of services in the EU.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; passenger traffic; car sharing; privatization; European Court of Justice; court decision; transportation industry; information brokerage